A novel reusable superhydrophilic NiO/Ni mesh produced by a facile fabrication method for superior oil/water separation. Issue 22 (11th May 2017) - Yu, Zhenwei; Yun, Frank F.; Gong, Zhiyuan; Yao, Qiang; Dou, Shixue; Liu, Kesong; Jiang, Lei; Wang, Xiaolin
Abstract : A low-cost and reusable novel superhydrophilic and underwater superoleophobic NiO/Ni mesh with a micro/nanoscale hierarchical structure exhibits superior oil/water separation in harsh environments. Abstract : There is a critical need to develop durable and reusable materials for oil–water separation, especially in harsh environments. Traditional anti-fouling mesh-based separation technologies are not reusable and limited by poor temperature resistance. Here we report a novel superhydrophilic and underwater superoleophobic NiO/Ni mesh which shows superior oil/water separation in harsh environments, with reusable and durable properties that can separate different oil–water mixtures with and without sand and soil contaminants, a >99% separation efficiency and up to 5.4 × 10 4 L m −2 h −1 permeate flux. The material is able to retain its superior performance over the 20 cycles we measured and for mixtures of sticky oils its performance is easily recoverable after a quick heat treatment. Our separation methodology is solely gravity-driven and consequently is expected to be highly energy-efficient. We anticipate that our separation methodology will have numerous applications, including in the clean-up of oil spills, wastewater treatment and other harsh condition oil–water separations.